Baseball America 2026 Almanac - Cooper, J.J; Woodiel, Carter; Norris, Josh; Eddy, Matt (Matthew); Cano, Jesús (Baseball journalist); Collazo, Carlos A.; Rudner, Jacob; Mates, Seth (Baseball America, 2026)
The only definitive baseball annual on the market, the Baseball America Almanac is a book whose value only grows year to year. It includes statistics and award winners for all levels of professional baseball with summaries and stats from the majors, minors, partner leagues, college baseball, foreign leagues and international competition. It covers what happened in baseball all around the globe in 2025.